Connectivity in times of control: writing/undoing/unpacking/acting out power performances. - Whitney Stark; Beatriz Revelles-Benavente; Olga Cielemecka (Sage, 2022)
In this collectively written article, the authors interrogate contemporary power constellations that run between control and connectivity. Regimes of individualism, hierarchies of assumed classifications and imperialistic subjectivities sustain the basis for political control that organises connections and divisions used to justify hierarchical dominations and distributions. This makes anti-oppression practices that value differing forms of connectivity and intra-dependence (between humans, more than humans, disciplines, all things considered to be of different bodies) nearly unimaginable. The authors offer/reconfigure/understand connectivity as a practice acting in and at odds with those controlling political regimes that organise and classify matter(s), while experimenting with their own writing methodology aimed at staying connected. Informed by new materialist feminist practices and ideas, the authors discuss the political stakes of multiple ideas of connectivity within three empirical scenarios: academic labour practices, social media and a digitally established mutual aid community. We trace entangled forces of separation and control shaped by global imperialism, processes of individuation and technological apparatuses and how they perform within these scenarios. This approach is mirrored in our practice of writing together. In an alternative to traditionalised ways of writing, we expand upon an embodied praxis, elaborating on multiple engagements while offering our own connections with these differing situated knowledges. In light of this, the authors write in a diffractive, collective fashion that lies somewhere between a conversation and the strict linearity of typical narratives.